DESKRIPTIF FAKTOR-FAKTOR YANG MEMPENGARUHI WANITA USIA SUBUR (WUS) TIDAK MENGGUNAKAN ALAT KONTRASEPSI - Astuti, Eni; ., Ratifah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Many women have difficulty in determining the types of contraceptive choice due to limited knowledge of the requirements and safety methods kontrasepsi.Tidak no single method of contraception is safe and effective for all the clients. Therefore, various factors should be considered carefully about the benefits and side effects of contraceptive use. Support your husband is one of the socio-cultural variables that contribute significantly to the use of contraceptives for women. Knowing descriptive factors affecting WUS not using contraception at the Work Area Health Center Donates Banyumas in 2013. The study was a descriptive cross-sectional approach. The population in this study were all WUS are not using contraception on Donate Work Area Health Center. Total population of 154 people. Sample of 61 people. Parity primiparous has the highest number of respondents ie 33 (54.10%). Respondents' knowledge about contraceptive side effects are pretty much the majority of 42 respondents (68.85%). Most husbands do not support the use of contraceptives by 52 respondents (85.25%). The majority of respondents have parity primiparous, have sufficient knowledge about the side effects of contraception and the husband does not support the use of contraceptives. Keywords: WUS, not using contraception